РЕЗУЛЬТАТЫ ОБЪЕКТИВНОЙ АККОМОДОМЕТРИИ ПРИ СОДРУЖЕСТВЕННОМ КОСОГЛАЗИИ - E. P. Tarutta; N. A. Aklaeva; T. Yu. Larina; N. A. Tarasova; T. Z. Khvedelidze; N. Yu. Kushnarevich (Российский офтальмологический журнал, 2018)
Purpose. This paper presents the results of objective accommodation measurements taken from patients with concomitant strabismus. Materials and methods. The experiment was performed on 32 patients (64 eyes) ranging from 5-26 years of age (in average 13.5 ± 1.43 years old): 26 patients with esotropia (52 eyes), 2 patients with exotropia (4 eyes), and 4 patients with secondary strabismus (8 eyes). 8 of the patients (10 eyes) identified amblyopia of various degrees. 51 of the eyes exhibited hyperopia from 0.5 to 9.5 D according to spherical equivalent refraction, and 16 eyes exhibited myopia from 0.25 to 10 D. The control group consisted of 30 children with hyperopia (16 eyes), emmetropia (10 eyes), and myopia of various degrees (34 eyes) without strabismus. To determine specific indicators of objective accommodation - Binocular (BAR) and Monocular Accommodative Response (MAR), the options of consensual accommodation, as well as the resting state of accommodation (RSA) in concomitant strabismus - the open field autorefkeratometer Grand Seiko WR - 5100K was used. The degree of deviation was determined using the Hirschberg test and a handheld ophthalmoscope. Results. The MAR ranged between normal and drastically lower values averaging at -1.85 ± 0.1 D. The BAR averaged at 2.23 ± 0.1 D and was greater than the MAR in half of the measured cases (61.3 %). The interocular difference in the BAR reached 2.95 D, averaging at 0.87±0.14 D. The interocular difference in MAR reached 0.85 D, averaging at 0.34 ± 0.07 D. In the control group, BAR values were lower than MAR; the interocular differences consisted of 0.13 ± 0.01 and 0.08 ± 0.01 D, respectively. Highly amblyopic eyes had equal and drastically decreased BAR and MAR (average of -0.16 ± 0.07 D); in the fellow eyes, BAR and MAR were higher -1.08 ± 0.14 and -1.0 ± 0.14 D, respectively. In esotropic eyes, RSA was higher in the misaligned eye, and in exotropic eyes, RSA was lower in the misaligned eye. The straight and concomitant responses were decreased: until -1.43 ± 0.1 and -1.32 ± 0.15 D respectively. In the control group, the straight and concomitant accommodative response was similar (average of -1.77 ± 0.17 D in both cases). Conclusion. The results showed the characteristic changes in accommodative parameters as a result of heterotropia, not typical for orthotropic patients with various types of refraction // Russian Ophthalmological Journal, 2017; 1: 49-54. doi: 10.21516/2072-0076-2017-10-1-49-54.